Dietary Bioactive Peptide Alanyl-Glutamine Attenuates Dextran Sodium Sulfate-Induced Colitis by Modulating Gut Microbiota. (10th May 2021) - Xu, Qingbiao; Hu, Mingyang; Li, Min; Hou, Jinxiu; Zhang, Xianghua; Gao, Ya; Chachar, Bahram; Li, Xiang
Abstract : Inflammatory bowel disease (IBD) is a chronic intestinal disorder threatening human health. Di-peptide alanyl-glutamine (Ala-Gln) has various beneficial effects on gut health. However, its role and functional mechanism in treating IBD are still not clear. Therefore, the protective effects of Ala-Gln and glutamine (Gln) on dextran sulfate sodium- (DSS-) induced colitic mice were investigated in this study. The results showed that oral supplementation of Ala-Gln or Gln significantly attenuated the colitis symptoms in mice, including body weight loss, colon length, disease activity index, histological scores, and tissue apoptosis. The concentrations of interleukin- (IL-) 1 β, IL-6, tumor necrosis factor- α, and myeloperoxidase were significantly decreased, while the concentrations of immunoglobulins (IgA, IgG, and IgM) and superoxide dismutase were significantly increased by Ala-Gln or Gln supplementation. The expression of occludin and peptide transporter 1 (PepT1) was significantly increased by Ala-Gln or Gln. Interestingly, Ala-Gln had better beneficial effects than Gln in alleviating colitis. In addition, 16S rDNA sequencing showed that the DSS-induced shifts of the microbiome (community diversity, evenness, richness, and composition) in the mouse colon were restored by Gln and Ala-Gln, including Lactobacillus, Bacteroides_acidifaciens, Bacteroidales, Firmicutes, Clostridia, Helicobacter, and Bacteroides . Correspondingly, the functions of the microflora metabolism pathways were also rescued by Ala-Gln, including fatty acid metabolism, membrane transporters, infectious diseases, and immune system. In conclusion, the results revealed that Ala-Gln can prevent colitis through PepT1, enhancing the intestinal barrier and modulating gut microbiota and microflora metabolites.